Isolation and Identification of Functional Bacillus Strain from Cupei of Sichuan Bran Vinegar and Evaluation of Its Fermentation Characteristics - Yuwei WU; Yu TIE; Zhixing TANG; Haiyan ZHU; Yuwei LI; Wenyou ZHU; Xinhui WANG; Liguo YIN (Shipin gongye ke-ji)
Bacillus bacteria are critical functional strains during fermentation of Sichuan bran vinegar that contribute to maintain the quality of vinegar. In this study, some functional Bacillus bacteria were isolated from the Cupei (grains undergoing acetic acid fermentation) of Sichuan bran vinegar, and the strains were identified by biochemical tests and 16S rRNA sequencing. The fermentation properties of these strains were studied, and the 5 Bacillus strains with great fermentation performance were discovered. They were identified as Paenibacillus cookii BA-6, Bacillus velezensis BA-9, Bacillus tropicus BB-5, Bacillus subtilis BB-13, and Calidifontibacillus erzurumensis BC-11. The five strains grew well at 30~40 ℃ and pH5~7 (OD600=0.23~0.52), with a certain degree of tolerance for environmental factor. Some of the Bacillus strains had a strong ability to hydrolyze protein (proteolytic ring of B. velezensis BA-9: 3.7±0.3) and starch (starch hydrolysis ring of P. cookie BA-6: 3.8±0.5). The simulated solid-state fermentation of inoculation with Bacillus and Acetobacter was carried out to investigate their potential use in industrial bran vinegar fermentation. Results showed that inoculation of P. cookie BA-6, B. velezensis BA-9, and C. erzurumensis BC-11 could increase total acid, lactic acid, acetic acid, and volatile flavor compounds content (e.g., phenyl ethanol, benzyl alcohol, isopentanol, and guaicol), further raise the overall fermentation quality of the Cupei. Overall, the 5 strains of Bacillus identified in the study were beneficial for the formation of flavor compounds during the Cupei fermentation of bran vinegar. The study provides a theoretical foundation for enhancing the quality of Sichuan bran vinegar.